THE PRESENT CONTINUOUS TENSE: A COMPREHENSIVE ANALYSIS OF FORM, FUNCTION, AND USAGE (Лучшие интеллектуальные исследования, 2025)
The present continuous tense, also known as the present progressive tense, is a fundamental aspect of English grammar that conveys actions happening at the moment of speaking or around the present time frame. This paper provides a comprehensive analysis of the present continuous tense, encompassing its formation, diverse functions, and nuanced usage within various contexts. The study explores the structural components of the tense, its role in expressing ongoing actions, temporary situations, and planned future events. Furthermore, the paper examines the present continuous in conjunction with other tenses, such as the simple present, to illustrate its significance in creating temporal contrasts and expressing dynamic actions. The paper also delves into common errors and difficulties encountered by English language learners, and offers pedagogical implications for effective teaching and learning of the present continuous tense. The paper also investigates the use of stative verbs within the present continuous context and the implications they carry.